Classification of pythagoras triples And How to generate them - Kumar, A.S.Mohan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Furthermore, the Pythagorean theorem is commonly used in advanced math today. It is used in computing surface areas, volumes and perimeters of different geometric shapes, converting between polar and rectangular coordinates and computing the distance between particular points on a plane. The Pythagorean Theorem can be used in any real life scenario that involves a right triangle having two sides with known lengths. In a scenario where a certain section of a wall needs to be painted, the Pythagorean Theorem can be used to calculate the length of the ladder needed if the height of the wall and the distance of the base of the ladder from the wall are known. The Pythagorean Theorem can be usefully applied because the relationship between the lengths of the sides in any right triangle is consistent. For example, in a baseball field, if the distance between each base is known, then the shortest distance to throw the ball from first base to third base can be calculated using the Pythagorean Theorem. When purchasing a television, the size advertised refers to the length of the diagonal of the television. If an old TV was being sold, the lengths of two of its sides can be used to calculate the length of the diagonal and thereby determine the size of the TV.